2015
DOI: 10.1098/rsif.2015.0685
|View full text |Cite
|
Sign up to set email alerts
|

Unreliable numbers: error and harm induced by bad design can be reduced by better design

Abstract: Number entry is a ubiquitous activity and is often performed in safety- and mission-critical procedures, such as healthcare, science, finance, aviation and in many other areas. We show that Monte Carlo methods can quickly and easily compare the reliability of different number entry systems. A surprising finding is that many common, widely used systems are defective, and induce unnecessary human error. We show that Monte Carlo methods enable designers to explore the implications of normal and unexpected operato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Conversion of a 1 mg dose of oral morphine to methadone resulted in a dose ranging from 0.05 to 0.67 mg methadone (a 13:1 range), with fewer than half the apps recognising that the conversion formula used should depend on the actual dose as well as on the drugs concerned. Thimbleby et al 2 found that the delete key on many apps does not work correctly, so ironically if a user tries to correct an error they notice, that correction may cause an error they do not notice. from app developers, the RCP Health Informatics Unit (HIU) has developed a short checklist (see Fig 1) to support clinicians wishing to assess the quality of apps.…”
Section: Analysis and Problem Statementmentioning
confidence: 99%
“…Conversion of a 1 mg dose of oral morphine to methadone resulted in a dose ranging from 0.05 to 0.67 mg methadone (a 13:1 range), with fewer than half the apps recognising that the conversion formula used should depend on the actual dose as well as on the drugs concerned. Thimbleby et al 2 found that the delete key on many apps does not work correctly, so ironically if a user tries to correct an error they notice, that correction may cause an error they do not notice. from app developers, the RCP Health Informatics Unit (HIU) has developed a short checklist (see Fig 1) to support clinicians wishing to assess the quality of apps.…”
Section: Analysis and Problem Statementmentioning
confidence: 99%
“…In general, health IT has been recognized for its direct link to patient safety [9] and poor usability or design of health IT has been identified as an important culprit in medical errors [10], including examples related to medication bar coding [11], physician order entry [12], and other safety domains [13]. More recently, safety concerns have been linked to EHRs in particular, specifically as they relate to workflow and data display [14].…”
Section: Introductionmentioning
confidence: 99%
“…Numeric user interfaces seem easy to implement, so it is surprising that many have bugs [13][14][15], perhaps a consequence of programmers thinking number entry is so easy to program they do not think it is worth adopting best practice they would use for problems recognised as being hard.…”
Section: Bugsmentioning
confidence: 99%
“…An unlimited number of bugs is possible, and any can interact badly with use error, so the recommendations for mitigation are to use formal methods [13] and testing [15], as well as development environments that support tools for rigorous development.…”
Section: Bugsmentioning
confidence: 99%
See 1 more Smart Citation